Odpowiedzi

2010-01-31T16:32:33+01:00
(√2x-1)(√2x+1)-(√2x-1)²+(x-√2)²=
(√2x)²-1-[(√2x)²-2√2x+1]+x²-2√2x+(√2)²=
2x-1-(2x-2√2x+1)+x²-2√2x+2=
2x-1-2x+2√2x-1+x²-2√2x+2=
x² dla= -√3
(-√3)²=3




a) (2x-1)²-(x-2)² =4x²-4x+1-(x²-4x+4)=4x²-4x+1-x²+4x-4=3x²-3

b) (x+2)²-3(x+1)(x-7)=x²+4x+4-3(x²-7x+x-7)=x²+4x+4-3x²+21x-3x+21= -2x²+22x+25

Najlepsza Odpowiedź!
2010-01-31T16:52:12+01:00
(/-pierwiastek)
wzory skróconego mnożenia:
(a-b)2=a2-2ab+b2
(a+b)2=a2+2ab+b2
(a-b)(a+b)=a2-b2

(√2x-1)(√2x+1)-(√2x-1)²+(x-√2)², gdy x= -√3
(√2x-1)(√2x+1)-(√2x-1)²+(x-√2)²=
(/2x)2-1-(2x2-2/2x+1)+(x2-2/2x+2)=
2x2-1-2x2+2/2x-1+x2-2/2x+2=x2
x2=(-/3)2=3

a) (2x-1)2-(x-2)2=(4x2-4x+1)-(x2-4x+4)=(4x2-4x+1-x2+4x-4)=
3x2-3
b)(x+2)2-3(x+1)(x-7)=(x2+4x+4)-3(x2-7x+x-7)=(x2+4x+4)-3(x2-6x-7)=
(x2+4x+4)-(3x2+18x+21)=x2+4x+4-3x2+18x+21=-2x2+22x+25